Constrictive Pericarditis Post‐Lung Transplant. Issue 8 (8th June 2015) - Stephens, Georgina; Bhagwat, Krishna; Marasco, Silvana; McGiffin, David
Abstract Constrictive pericarditis is a rare entity following lung transplant, with only seven previous cases reported in the literature. We present two additional cases and review the literature on this subject. Constrictive pericarditis should be considered in lung transplant patients who present with dyspnea and evidence of cardiac failure. Pericardiectomy remains the treatment of choice irrespective of the etiology. doi: 10.1111/jocs.12581 (J Card Surg 2015;30:651–655)